Super Subtotal Gastrectomy: A Novel Reconstruction Concept for Upper Gastric Cancer That Preserves the Fornix - Kohei Fujita; Hiroyuki Sagawa; Sunao Ito; Ryo Ogawa; Shuji Takiguchi (Annals of Gastroenterological Surgery)
ABSTRACT The incidence of upper‐third gastric cancer is rising, necessitating proximal gastrectomy or total gastrectomy in most patients. However, surgical removal of the fornix, a major site for ghrelin secretion, often results in reduced appetite and weight loss post‐surgery. To address this issue, we devised a resection approach aimed at preserving ghrelin secretory sites. Here, we introduce a novel technique for treating upper‐third gastric cancer near the esophagogastric junction: super subtotal gastrectomy (SSTG). During distal gastrectomy assisted by robotics, lymph node dissection was performed. Endoscopic confirmation of the tumor site guided the design of the gastrectomy line. Using a linear stapler, the stomach was dissected from the greater curvature fold to the angle of His. The specimen was then extracted through a precise incision from the angle of His to the right side of the esophagus, partially resecting the esophagogastric junction. Suturing of the open lumens of the esophagus and stomach was performed to repair the remaining stomach. Closure of the diaphragmatic crus prevented esophageal hiatal hernia. Reconstruction was achieved through Roux‐en‐Y reconstruction. SSTG offers the advantage of maintaining an oral margin beyond the esophageal junction while preserving the fornix. In the SSTG group, the median operative time was 333 min (range: 257–354), with a blood loss of 79.5 mL (range: 20–141). No serious intraoperative complications were observed. Our proposed SSTG technique enables the preservation of the fornix even in cases of upper‐third gastric cancer located closer to the esophagogastric junction than was previously possible.